HUBUNGAN ANEMIA PADA IBU HAMIL DENGAN BAYI BERAT BADAN LAHIR RENDAH (BBLR) DI RS CAMATHA SAHIDYA KOTA BATAM TAHUN 2017 - Mariany, Yuli (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Anemia in pregnant women is a condition with hemoglobin levels <11 gr% in trimesters 1 and 3 and hemoglobin levels <10.5 gr% in trimester 2. Anemia in pregnant women can potentially give birth to premature infants and low birth weight (LBW).Low birth weight is a baby with birth weight less than 2500 g regardless of gestational age. This research is an observational analytic research with cross sectional design. The sample is 71 anemic patient’s in pregnant women who experienced baby LBW. Data’s taken from medical record and univariate and bivariate analyzed using chi-square. The result of the research showed anemia in pregnant woman with LBW (65,7%), anemia in pregnant woman with not BBLR (34,3%), not anemia in pregnant woman with LBW (97,2%) and not anemia in pregnant women with no BBLR (2.8%).There is found a significant relationship between anemia in pregnant women with LBW with p value = 0.001 (p <0.05). From the research results can be concluded there is a meaningful relationship between anemia in pregnant women with LBW.